Investigation of long chain omega‐3 PUFAs on arterial blood pressure, vascular reactivity and survival in angiotensin II‐infused Apolipoprotein E‐knockout mice. (February 2016) - Bürgin‐Maunder, Corinna S; Nataatmadja, Maria; Vella, Rebecca K; Fenning, Andrew S; Brooks, Peter R; Russell, Fraser D
Summary: Abdominal aortic aneurysm (AAA) is an inflammatory vascular disease. Long chain omega‐3 polyunsaturated fatty acids (LC n‐3 PUFAs) decrease inflammation and oxidative stress in an angiotensin II‐infused apolipoprotein E‐knockout (ApoE −/− ) mouse model of AAA. This study investigated the effects of LC n‐3 PUFAs on blood pressure and vascular reactivity in fourteen angiotensin II‐infused ApoE −/− male mice. Blood pressure was obtained using a non‐invasive tail cuff method and whole blood was collected by cardiac puncture. Vascular reactivity of the thoracic aorta was assessed using wire myography and activation of endothelial nitric oxide synthase (eNOS) was determined by immunohistochemistry. A high LC n‐3 PUFA diet increased the omega‐3 index and reduced the n‐6 to n‐3 PUFA ratio. At day 10 post‐infusion with angiotensin II, there was no difference in systolic blood pressure or diastolic blood pressure in mice fed the high or low n‐3 PUFA diets. The high LC n‐3 PUFA diet resulted in a non‐significant trend for delay in time to death from abdominal aortic rupture. Vascular reactivity and eNOS activation remained unchanged in mice fed the high compared to the low LC n‐3 PUFA diet. This study argues against direct improvement in vascular reactivity in ApoE −/− mice that were supplemented with n‐3 PUFA for 8 weeks prior to infusion with angiotensin II.